The Role of Information and Communication Technology on Tax Revenue in Indonesia - Moslem Afrizal; Khoirunurrofik Khoirunurrofik (Jurnal Ekonomi Pembangunan)
Taxes are a fundamental component of the economy, serving as a primary resource of revenue for governments across the globe. Tax revenues are essential for financing public expenditures such as education, healthcare, and infrastructure. This study aims to analyze the indirect relationship between information and communication technology (ICT) and tax revenue in Indonesia, specifically through tax compliance. We select ICT due to its established role as an integral part of society and helps streamline tax administration, including payment, reporting, and auditing. The data used in this study comprise panel data at the provincial level from 2018 to 2022. The tax indicator used is the tax ratio, while the ICT indicators include base transceiver station (BTS) infrastructure, and internet penetration. Utilizing the two-stage least squares (TSLS) method, this study finds that ICT has a positive correlation with the compliance ratio, and the compliance ratio, in turn, has a positive correlation with tax revenue. The implications of this study suggest the expansion of telecommunications infrastructure coverage across all regions of Indonesia and the utilization of technology in disseminating tax information to continually improve tax compliance and tax revenue mobilization.